Regulation of host cell survival by intracellular Plasmodium and Theileria parasites - HEUSSLER, V.; STURM, A.; LANGSLEY, G. (Parasitology, 2006)
Plasmodium and Theileria parasites are obligate intracellular protozoa of the phylum Apicomplexa. Theileria infection of bovine leukocytes induces transformation of host cells and infected leukocytes can be kept indefinitely in culture. Theileria-dependent host cell transformation has been the subject of interest for many years and the molecular basis of this unique phenomenon is quite well understood. The equivalent life cycle stage of Plasmodium is the infection of mammalian hepatocytes, where parasites reside for 2–7 days depending on the species. Some of the molecular details of parasite-host interactions in P. berghei-infected hepatocytes have emerged only very recently. Similar to what has been shown for Theileria-infected leukocytes these data suggest that malaria parasites within hepatocytes also protect their host cell from programmed cell death. However, the strategies employed to inhibit host cell apoptotic pathways appear to be different to those used by Theileria. This review discusses similarities and differences at the molecular level of Plasmodium- and Theileria-induced regulation of the host cell survival machinery.